Correlation between low-frequency noise and interface traps of fully-depleted silicon-on-insulator tunneling FETs induced by hot carrier stress. (1st October 2020) - Shin, Hyun-Jin; Song, Hyun-Dong; Song, Hyeong-Sub; Eadi, Sunil Babu; Choi, Hyun-Woong; Kim, Seong-Hyun; Kim, Do-Woo; Lee, Hi-Deok; Kwon, Hyuk-Min
Abstract: The generation of interface traps at the drain corner during hot-carrier-stress (HCS) in a fully-depleted silicon-on-insulator tunneling field-effect transistor (TFET) was invested and correlated to low-frequency noise performance. The hot carrier damage increases the number of the generated interface traps because hot carriers could gain high kinetic energy to reach the conduction band near the drain region in TFET. Unlike the results of channel-HCS characteristics in MOSFETs, the frequency exponent γ under the same stress voltage conditions in TFET decreased by 21.4%, which was attributed by the generation of interface traps as compared to deeper border traps.